2021
DOI: 10.36892/ijlts.v2i1.105
|View full text |Cite
|
Sign up to set email alerts
|

Discovering Writing Difficulties of Malay ESL Primary School Level Students

Abstract: Writing is perceived to be one of the most difficult skills for English language learners to master. Although studies on challenges faced by ESL students in writing are replete, most of them have focused on students at secondary and tertiary levels of education. Studies on learners at lower level have been scarce. Thus, this paper aims to fill the gap by examining the major problems faced by ESL primary school level students in writing in English. Survey and interview sessions were conducted to fit the purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…They take a long time to use new vocabulary in writing (30% of respondents) and find it difficult to combine logical sentences (36%). This finding is in line with previous research from (Ghulamuddin et al, 2021;Habibi, 2017;Keong & Mussa, 2015) which found that in writing, lack of vocabulary is one of the obstacles that students meet, making it difficult for them to write what's on their mind.…”
Section: Discussionsupporting
confidence: 91%
“…They take a long time to use new vocabulary in writing (30% of respondents) and find it difficult to combine logical sentences (36%). This finding is in line with previous research from (Ghulamuddin et al, 2021;Habibi, 2017;Keong & Mussa, 2015) which found that in writing, lack of vocabulary is one of the obstacles that students meet, making it difficult for them to write what's on their mind.…”
Section: Discussionsupporting
confidence: 91%
“…Studies that concentrated on students at the lower level or younger generation is very limited. (Ghulamuddin et al, 2021). This is also well supported in a study conducted by Rashid, Yunus & Wahi (2019) whereby they too have highlighted that future studies needed to be conducted in different levels of students utilising the Padlet to yield more results.…”
Section: Related Past Studiesmentioning
confidence: 58%
“…Hence, to compose good narrative writing, the key elements play a central role (Selvaraj et al, 2020). However, to write a good or improve their narrative writing, students need more exercises (Ghulamuddin et al, 2021).…”
Section: Narrative Writing Skillsmentioning
confidence: 99%